Novel complex nanostructure from directed assembly of block copolymers on incommensurate surface patterns - Kim, Sang Ouk; Kim, Bong Hoon; Meng, Dong; Shin, Dong Ok; Koo, Chong Min; Solak, Harun H.; Wang, Qiang (WILEY-V C H VERLAG GMBH, 2007)
A novel complex nanostructure, produced by the directed assembly of a block copolymer thin film on chemically patterned surfaces, is presented. The new nanostructure, which consists of cylinders oriented alternately parallel and perpendicular to the surface (see figure, a result of self-consistent field calculations), demonstrates that a judiciously designed chemical pattern may be used to fabricate a well-ordered complex nanostructure in block copolymer thin films.
Keywords: CONSISTENT-FIELD THEORY; THIN-FILMS; NANOLITHOGRAPHY; ORGANIZATION; LITHOGRAPHY; SIMULATIONS; FABRICATION; MONOLAYERS; TEMPLATES; BLENDS